Visual and acoustic communication signals in birds - taxonomy, evolution and transfer between signals mediated by sensory drive (2016)
The evolution of communication signals is a central, integrative topic in evolutionary biology. In this dissertation, I propose that achieving a comprehensive understanding of the evolution of such signals requires not only considering different theories in isolation (i.e. the transfer and sensory drive hypotheses), but also possible interactions between theories and disciplines. For example, the negative association between communication signals observed by Darwin might be strongly determined by adaptation for communication to different habitats: Each habitat has its own features affecting the efficacy of communication, and animals should evolve strategies to optimize signal salience in the face of resolving potential tradeoffs. Based on this overall framework we tested hypothesis about the evolution of and relationships between acoustic and visual signals in relation to habitat features. I used birds as a model system, but the approach and conclusions likely apply to other animals using both acoustic and signals for communication. Specifically, this work focused on three different study systems which allowed me to approach the relationships between types of signals from different perspectives: (1) two species complexes in the tinamou family (Tinamidae) differing in patterns of variation in plumage and vocalizations, (2) a widely distributed family of passerine birds with species exhibiting different communication strategies and occurring in contrasting habitats (i.e the New World warblers, Parulidae), and (3) an assemblage of multiple species coexisting locally in tropical montane forest site. Additionally, i explored the use and relevance of information contained in sound collections for studies on the ecology and evolution of animal communication